Seismic Vulnerability Assessment of Deficient RC Structures with Bar Pullout and Joint Shear Degradation - Arslan Mushtaq; Shaukat Ali Khan; Hamza Farooq Gabriel; Sajjad Haider (Advances in Civil Engineering)
Pakistan is an underdeveloped country, still striving for improvement in construction practices. Most of the private construction is carried out as nonengineered which caused loss of approximately 85,000 lives in Kashmir (2005) earthquake. However, after the Kashmir (2005) earthquake, the government and engineering community emphasized on implementation of seismic codes. Although the current construction practices are considered as better than previous construction work the vulnerability of these structures is yet to be determined. It aims at the vulnerability assessment of recent RC construction in Pakistan that still needs to be assessed. Research work starts with calibration of panel zone element (PERFORM 3D) depicting joint shear degradation, while comparing the analytical results with experimental work, found in the literature. The frame work is then used for vulnerability assessment of RC structures typical of current construction practices in Pakistan while using advanced capacity spectrum method, developed by Kyriakides for which three cases have been considered, being constructed more frequently by public sector, in different seismic zones, based on design usually followed by builders in the region. Finally, the conclusion is drawn with suggestion of further improvement of seismic behavior of the structures.